2021
DOI: 10.1002/edn3.184
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of eDNA metabarcoding approaches for sessile benthic surveying in the Kimberley region, north‐western Australia

Abstract: The application of environmental DNA technologies is a promising new approach to rapidly audit biodiversity across large-scale, remote regions. Here, we examine the efficacy of a dual-assay eDNA metabarcoding approach for sessile benthic bioassessments in the turbid waters of the Lalang-garram marine parks, Kimberley, north-western Australia. We ask three principal questions: (1) "Is the eDNA released by sessile benthic taxa (i.e., hard and soft corals, sponges and tunicates) locally detectable?", (2) "What le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…We presume that the similar taxonomic profiles across shallow depths may reflect coral mucus being constantly released (Wild et al, 2004b), often dominating suspended matter around reefs (Johannes, 1967; Marshall, 1968). The majority of this mucus usually dissolves in the water, but a fraction can form floating gel‐like mucus aggregates with positive buoyancy (Wild et al, 2004a). However, the residence time of this coral mucus (thus, eDNA) is thought to be low as aggregates trap particles and therefore decrease in buoyancy over time and sink (Wild et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presume that the similar taxonomic profiles across shallow depths may reflect coral mucus being constantly released (Wild et al, 2004b), often dominating suspended matter around reefs (Johannes, 1967; Marshall, 1968). The majority of this mucus usually dissolves in the water, but a fraction can form floating gel‐like mucus aggregates with positive buoyancy (Wild et al, 2004a). However, the residence time of this coral mucus (thus, eDNA) is thought to be low as aggregates trap particles and therefore decrease in buoyancy over time and sink (Wild et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of this mucus usually dissolves in the water, but a fraction can form floating gel‐like mucus aggregates with positive buoyancy (Wild et al, 2004a). However, the residence time of this coral mucus (thus, eDNA) is thought to be low as aggregates trap particles and therefore decrease in buoyancy over time and sink (Wild et al, 2004a). Due to this continuous cycle, sedimentation is estimated to occur within a few hours of release (Wild et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BRUV and eDNA metabarcoding techniques detected distinct fish communities, with some species recovered only by a single method indicating that a combined approach is desired if the goal is to capture total community diversity in these intertidal habitats. West et al (2021) and Dugal et al (2021) focus on an important coral reef network in the Kimberley region of northwestern Australia. Specifically, they showed that eDNA metabarcoding of the ITS2 region resulted in high rates of detection at the species and genus level for the habitat building scleractinian corals (Dugal et al, 2021;West et al, 2021), as well as other benthic invertebrates such as sponges and tunicates (West et al, 2021).…”
Section: B Iodiver S It Y Monitoringmentioning
confidence: 99%
“…West et al (2021) and Dugal et al (2021) focus on an important coral reef network in the Kimberley region of northwestern Australia. Specifically, they showed that eDNA metabarcoding of the ITS2 region resulted in high rates of detection at the species and genus level for the habitat building scleractinian corals (Dugal et al, 2021;West et al, 2021), as well as other benthic invertebrates such as sponges and tunicates (West et al, 2021).…”
Section: B Iodiver S It Y Monitoringmentioning
confidence: 99%
See 1 more Smart Citation